Evaluación del funcionamiento de un motor de combustión de encendido provocado bajo distintas condiciones atmosféricas para la obtención del mapa de consumo de combustible característico’ - González Plua, Steven Alexander (2022)
Vehicles that are commercialized worldwide are tested in laboratories where they are tested under standard operating conditions, even so, it is not possible to cover the widest range of operation in vehicles, because the actual conditions of the vehicle and the engine when traveling on the road vary constantly. This research project was carried out with the purpose of analyzing and determining the variation in the specific fuel consumption of a light automobile traveling on the Ventanas - Guanujo route, through the execution of experimental tests under real conditions, due to the incidence of the slope and the constant variation of the terrain, in addition to the change in atmospheric conditions from one point to another, in order to determine the fuel consumption and graphs of the map of the specific fuel consumption of a vehicle when traveling on a high gradient route. The data obtained in the investigation were used for the realization and analysis of the different graphs where the behavior of the engine is observed through the characteristic curves, the atmospheric conditions of the route, the variation of altitude, temperature and atmospheric pressure, and finally with the help of Minitab software, it was possible to graph and obtain the contour map showing the specific fuel consumption of the experimental tests carried out. It was possible to determine that the test in which a minimum value in fuel consumption was calculated was test 4, as a result 9,64 liters of fuel were consumed per hour, which also translates to 15,61 liters of fuel consumed per 100 kilometers, for the specific fuel consumption of the brake a value of 152,31 gkWH was calculated, which is in the minimum range of the fuel consumption map of this document. Key words: Specific fuel consumption, Driving cycles, Atmospheric conditions.